2022
DOI: 10.12659/msm.936335
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant System and Ions Concentrations After Femoral Neck and Resurfacing Hip Arthroplasty

Abstract: Background Oxidative stress is a disruption of the pro-oxidative-antioxidant balance, caused by excessive production or ineffective removal of reactive oxygen species. Material/Methods The study included 42 male patients aged 38 to 69 years. The first group consisted of 21 men with osteoarthritis after primary hip arthroplasty using the Smith & Nephew Birmingham Hip Resurfacing implant. The second group included 21 men after hip arthroplasty using the femoral neck SPIRO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 41 publications
(42 reference statements)
1
4
0
Order By: Relevance
“…Our results agree with other studies showing the absence of a relationship between Cr and Co blood concentrations and several markers of oxidative stress in patients with M-M THA and resurfacing [48,[60][61][62]. Another study comparing M-M hip resurfacing with C-C THA showed increased oxidative stress markers in the resurfacing patients [59]. The discrepancies observed between the aforementioned studies could be related to methodological differences in evaluating oxidative stress.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our results agree with other studies showing the absence of a relationship between Cr and Co blood concentrations and several markers of oxidative stress in patients with M-M THA and resurfacing [48,[60][61][62]. Another study comparing M-M hip resurfacing with C-C THA showed increased oxidative stress markers in the resurfacing patients [59]. The discrepancies observed between the aforementioned studies could be related to methodological differences in evaluating oxidative stress.…”
Section: Discussionsupporting
confidence: 89%
“…In a patient undergoing hip replacement revision with elevated blood and urinary concentrations of Cr and Co, an association was reported between metallosis and increased expression of NADPH-Oxidase 4 (NOX4), a well-known compound responsible for ROS generation in muscle tissue [23]. Other studies have suggested a relationship between metallosis and oxidative stress [24,25,59]. According to these reports, our initial hypothesis was that the patients with M-M, with higher Cr and Co levels than the C-M group and the control group, should have greater systemic oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surgical trauma triggers imbalances in various factors within the patient's body. Trauma and pain induce oxidative stress and inflammatory responses in the body (Ochocki et al, 2022). Postoperative patients in orthopedics experience localized pain and restricted mobility, which can contribute to complications such as pneumonia, venous thrombosis, and pressure ulcers.…”
Section: Discussionmentioning
confidence: 99%